Rental Price Prediction of Boarding Houses in Batam City Using Linear Regression and Random Forest Algorithms - Jerry, Jerry; Christian, Yefta; Herman, Herman (Politeknik Negeri Batam, 2023)
Boarding houses, commonly known as